The preparation temperature influences the physicochemical nature and activity of nanoceria - Yokel, Robert A.; Wohlleben, Wendel; Keller, Johannes Georg; Hancock, Matthew L.; Unrine, Jason M.; Butterfield, D. Allan; Grulke, Eric A. (Beilstein Journal of Nanotechnology, 2021)
Cerium oxide nanoparticles, so-called nanoceria, are engineered nanomaterials prepared by many methods that result in products with varying physicochemical properties and applications. Those used industrially are often calcined, an example is NM-212. Other nanoceria have beneficial pharmaceutical properties and are often prepared by solvothermal synthesis. Solvothermally synthesized nanoceria dissolve in acidic environments, accelerated by carboxylic acids. NM-212 dissolution has been reported to be minimal. To gain insight into the role of high-temperature exposure on nanoceria dissolution, product susceptibility to carboxylic acid-accelerated dissolution, and its effect on biological and catalytic properties of nanoceria, the dissolution of NM-212, a solvothermally synthesized nanoceria material, and a calcined form of the solvothermally synthesized nanoceria material (ca. 40, 4, and 40 nm diameter, respectively) was investigated. Two dissolution methods were employed. Dissolution of NM-212 and the calcined nanoceria was much slower than that of the non-calcined form. The decreased solubility was attributed to an increased amount of surface Ce4+ species induced by the high temperature. Carboxylic acids doubled the very low dissolution rate of NM-212. Nanoceria dissolution releases Ce3+ ions, which, with phosphate, form insoluble cerium phosphate in vivo. The addition of immobilized phosphates did not accelerate nanoceria dissolution, suggesting that the Ce3+ ion release during nanoceria dissolution was phosphate-independent. Smaller particles resulting from partial nanoceria dissolution led to less cellular protein carbonyl formation, attributed to an increased amount of surface Ce3+ species. Surface reactivity was greater for the solvothermally synthesized nanoceria, which had more Ce3+ species at the surface. The results show that temperature treatment of nanoceria can produce significant differences in solubility and surface cerium valence, which affect the biological and catalytic properties of nanoceria.
Keywords: cerium; dissolution; nanoparticles; physicochemical properties; valence state